2005
DOI: 10.1902/jop.2005.76.6.1006
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence as a Determinant of Toothbrushing Frequency and Level of Oral Hygiene

Abstract: Our results suggest that a weak sense of coherence increases both the probability of having a poor level of oral hygiene and a frequency of toothbrushing of less than once a day. This and the theory concerning the development of SOC suggest that sense of coherence may be taken as a determinant of both the frequency and the quality of toothbrushing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 24 publications
10
65
1
1
Order By: Relevance
“…The mean SOC score was lower among those who failed school more often and those who lived with a greater number of people (Table 2). The results presented a positive association between higher SOC and lesser dental caries experience, which is in agreement with data described in previous investigations [15,[22][23][24]. The authors of a pioneering study found that SOC was associated with dental caries, periodontal disease, oral hygiene and oral health behaviors, with a high SOC score constituting an important psychosocial factor related to oral health [15].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The mean SOC score was lower among those who failed school more often and those who lived with a greater number of people (Table 2). The results presented a positive association between higher SOC and lesser dental caries experience, which is in agreement with data described in previous investigations [15,[22][23][24]. The authors of a pioneering study found that SOC was associated with dental caries, periodontal disease, oral hygiene and oral health behaviors, with a high SOC score constituting an important psychosocial factor related to oral health [15].…”
Section: Resultssupporting
confidence: 91%
“…The authors of a pioneering study found that SOC was associated with dental caries, periodontal disease, oral hygiene and oral health behaviors, with a high SOC score constituting an important psychosocial factor related to oral health [15]. Subsequent studies also indicated a high SOC score to be a determinant factor of oral health [22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…Significant inverse associations were also found between mothers' SOC and children's levels of dental caries and gingival bleeding 15 . Other studies have shown a positive relationship between strong SOC and oral health related-quality of life 40 , frequency of tooth brushing 41 , as well as pattern and frequency of dental attendance 39,42 . Furthermore, SOC was related to functional status in a group of patients that received surgical treatment for oral or pharyngeal cancer.…”
Section: Sense Of Coherence and Healthmentioning
confidence: 89%
“…8,10,12,13,14,30 However, the investigation of the relationship of the SOC with clinical health conditions is still scant in the literature. Freire et al 5 found an association between SOC and cavities in the posterior teeth of adolescents, a result that was not confirmed by multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…According to Antonovsky,3 SOC is "a global orientation that expresses the extent to which one has a pervasive, enduring though dynamic feeling of confidence that (1) the stimuli from one's internal and external environments in the course of living are structured, predictable, and explicable; (2) the resources are available to one to meet the demands posed by these stimuli; and (3) these demands are challenges, worthy of investment and engagement". 3 The SOC has been shown to be a promising resource for establishing healthy behaviors 4,5,6,7,8,9,10,11,12,13,14,15,16 and a positive self-perception of oral health, 14,16 which increases the interest in investigating its relationship…”
Section: Introductionmentioning
confidence: 99%